Two Distinct Conformations in 34 FliF Subunits Generate Three Different Symmetries within the Flagellar MS-Ring - Norihiro Takekawa (American Society for Microbiology, 2021)
The bacterial flagellum is a motility organelle formed by tens of thousands of protein molecules. At the earliest stage of flagellar assembly, a transmembrane protein, FliF, forms the MS-ring in the cytoplasmic membrane as the base for flagellar assembly.